FAKTOR PENYAKIT YANG BERHUBUNGAN DENGAN KEMATIAN BALITA DI RUMAH SAKIT UMUM DAERAH KABUPATEN MUNA PROVINSI SULAWESI TENGGARA TAHUN 2021 - S.Sit.,M.Kes, Rosminah Mansyarif (NHM PRESS, 2021)
Under five mortality (1-4 Years) is the death of population aged 1 year up to 5 year or excactly 1 year up to 4 years 11 months and 29 days old. The aim of this study is to investigate if there is any association between febrile convulsion, malnutrition, dengue fever, diarrhea, and pneumonia with child under 5 mortality in Muna Regency Hospital in 2021. The methodology of the analysis employed a case control approach. A total sampling technique was also used to gather 30 positive cases and random sampling technique was used to gather control case. The data was collected through analysis of patient medical case records at the hospital. Univariate and bivariate data analysis method. Results showed that child mortality in Muna Regency Hospital based on febrile convulsion were 26,68%, malnutrition were 3,33%, dengue fever were 13,33%, diarrhea were 3,33%, pneumonia were 30%, and death caused by other factors were 23,33%. The association between disease factors with under-five mortality showed different result. Febrile convulsion shown p = 0,026, malnutrition shown p = 0,103, dengue fever shown p = 0,041, diarrhea shown p = 0,353, pneumonia shown p = 0,045, other factors shown p = 0,747. In conclusion results showed that there is a significant association between febrile convulsion and child mortality (p = 0,032 and OR = 10,545), there is a significant association between dengue fever and child mortality (p = 0,025), there is also a significant link between pneumonia and child mortality (p = 0,032 dan OR 6.000).